Систематична структура адвентивної фракції флори Волинської височини - Гуцман, Марія; Гуцман, Сергій; Guzman, Mariya; Guzman, Sergii (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті подано результати дослідження адвентивної фракції флори Волинської височини, яка налічує 446 видів неаборигенної флори, що належать до 270 родів і 79 родин. Аналіз рейтингу провідних родин адвентивної фракції флори Волинської височини свідчить про значний вплив Давнього Середземноморяʼя на формування сучасної спонтанної флори регіону. Одночас помічено наявність у спектрі провідних родин вихідців із Американського континенту. The article shows the results of research of the flora’s foreign group of Volyns’ka Upland, which has 446 species belonging to 270 genera and 79 families. These results point out to essential changes in composition and structure of flora and plant groups. Rating analysis of the leading families of the flora’s foreign group of Volyns’ka Upland affirms an essential influence on contemporary foreign flora of the Ancient Mediterranean region. At the same time the representation in the spectrum of leading emigrant families from American continent is visible. Foreign flora of Volyns’ka Upland embraces nearly the third part of specific diversity of flora in the region. Being in the conditions of transformation, native flora undergoes significant changes because of entry and naturalization of foreign species. They cause displacement of its main indices to the side, which is more characteristic to arid regions of the planet and level its zonal lines.
Systematic Structure of the Foreign Group of Floraof Volyns’ka Upland.
Keywords: систематична структура; адвентивні види; Волинська височина; systematic structure; alien species; Volyns’ka Upland